Stimuli‐Responsive Manganese Single‐Atom Nanozyme for Tumor Therapy via Integrated Cascade Reactions. (11th March 2021) - Zhu, Yang; Wang, Wenyu; Cheng, Junjie; Qu, Yunteng; Dai, Yi; Liu, Manman; Yu, Jianing; Wang, Chengming; Wang, Huijuan; Wang, Sicong; Zhao, Chao; Wu, Yuen; et al.
Abstract: The single‐atom enzyme (SAE) is a novel type of nanozyme that exhibits extraordinary catalytic activity. Here, we constructed a PEGylated manganese‐based SAE (Mn/PSAE) by coordination of single‐atom manganese to nitrogen atoms in hollow zeolitic imidazolate frameworks. Mn/PSAE catalyzes the conversion of cellular H2 O2 to . OH through a Fenton‐like reaction; it also promotes the decomposition of H2 O2 to O2 and continuously catalyzes the conversion of O2 to cytotoxic . O2 − via oxidase‐like activity. The catalytic activity of Mn/PSAE is more pronounced in the weak acidic tumor environment; therefore, these cascade reactions enable the sufficient generation of reactive oxygen species (ROS) and effectively kill tumor cells. The prominent photothermal conversion property of the amorphous carbon can be utilized for photothermal therapy. Hence, Mn/PSAE exhibits significant therapeutic efficacy through tumor microenvironment stimulated generation of multiple ROS and photothermal activity. Abstract : A manganese single‐atom enzyme (Mn/PSAE) was synthesized, which can efficiently catalyze the concurrent generation of . OH and . O2 − in tumor microenvironment. Moreover, amorphous carbon‐based Mn/PSAE has excellent NIR‐photothermal performance, which makes it possible to combine the multi‐catalytic and photothermal‐enhanced tumor therapy.